OPGRAWINGS IN DIE STAD VAN DAWID = EXCAVATIONS IN THE CITY OF DAVID - Pienaar, Daniel N. (Scriptura, 1983)
The article is a report on the last six seasons of archaeological excavations in the City of David under the leadership of Professor Shiloh of the Archaeological Institute of the Hebrew University in Jerusalem. The author himself participated in these excavations and is therefore able to give a first-hand report of the progress and most important results. After a survey of previous work in the City of David, the specific aims of the present expedition which commenced on July 2, 1978, are summarized. Consequently, the various areas of the dig itself are described (G, J, E, D, B, A and H), with a discussion of the most important finds. The article concludes with a review of each of the last six seasons (1979-1983), including the results of the 1983 season, which have just become available. In a final section the author points out the importance of these excavations for students and teachers of Biblical Studies.